Total Knee Replacement in the Obese Patient: Comparing Computer Assisted and Conventional Technique - Yogeesh D. Kamat; Kamran M. Aurakzai; Ajeya R. Adhikari (The Scientific World Journal)
Purpose. Obesity is being considered a “global epidemic.” Surgical procedures are rendered more difficult in obese patients. We aimed to see whether any benefits were evident with use of computer navigation during total knee replacement in these cases. Methods. A retrospective analysis of 287 TKR performed by a single surgeon was undertaken, including 133 TKR undertaken with computer navigation and 154 using standard instrumentation. Each group was further divided into subgroups depending on whether the patients were obese or nonobese. Results. We found that TKR in obese patients took longer with standard instruments, but not with computer navigation. A chronological analysis revealed that the surgeon progressively got quicker using computer navigation to the point that there was no difference in time with either of the operative techniques in obese patients. The mid-term clinical outcomes at five years were similar. Computer navigated TKR were more consistently accurately aligned. Conclusions. In obese patients, a dual advantage is provided by computer navigation: better alignment and no time penalty.